Exploring Learners' Emotions and Teachers' Strategies in Dealing with Them in EFL Contexts - Pertiwi, Canda Ayu Arum; Dzulfikri, Dzulfikri (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and Culture, 2023)
The study on emotions is particularly important as it is expected to influence people's overall health (Rezapour:2022), then it develops into guilt, embarrassment, shock, pride, and empathy. Based on their experience, this emotion will develop continuously; each of them has different ways of handling it. Understanding students’ emotion is important in the process of studying and receiving any knowledge. This research focuses on one of the private schools located in Malang city. The researchers carried out an interview for more or less sixteen until thirty minutes each, which means around 59 minutes in total. By using the Indonesian language, the researchers conducted the interview with all of the participants face-to-face. Some causes of students’ negative emotions appear such as 1) Do not like the teacher and the subject, 2) Unstable emotions, 3) Class conditions, and 4) Classmates’ Effect. Teachers need to fix students’ negative emotions so that the teaching and learning process will run smoothly.